Senyawa Bioaktif dan Antioksidan Buah Mangrove Sonneratia alba J.E. Smith dari Desa Lhok Bubon Kecamatan Samatoga Kabupaten Aceh Barat - Hayatun Nufus; Mohamad Gazali; Alaudin Alaudin; Asri Mursawal; Sri Wahyuni; Cut M.N. ‘Akla; Syahrial Syahrial; Neneng Marlian (Jurnal Kelautan Tropis, 2023)
The mangrove species Sonneratia alba is one of the plants that has good bioactive compounds and very easy to find. However, the content of bioactive compounds and nutrients from a plant is strongly influenced by internal and external factors. The study was conducted with the aim to know the proximate content, yield and antioxidant activity of S. alba fruit from Lhok Bubon Village, Samatoga District, West Aceh Regency. The extraction method used methanol, ethyl acetate and n-hexane as solvent with antioxidant test using DPPH solution (2,2-Diphenil-2-picryl hydrazil). The results of the study showed the proximate content consisted of water 30.71%, ash 5.06%, fat 8.59%, protein 3.48% and carbohydrate 52.16%. Meanwhile, the yield showed ethyl acetate solvent had the highest yield (69.11 ± 13.27%), then followed by n-hexane (68.38 ± 13.21%) and methanol (64.44 ± 14.78%). Furthermore, for the antioxidant activity of S. alba fruit from Lhok Bubon Village, Samatoga District, West Aceh Regency, overall it was classified as very strong IC50 < 50 ppm).